Beyond oil degradation: enzymatic potential of Alcanivorax to degrade natural and synthetic polyesters. (27th February 2020) - Zadjelovic, Vinko; Chhun, Audam; Quareshy, Mussa; Silvano, Eleonora; Hernandez‐Fernaud, Juan R.; Aguilo‐Ferretjans, María M.; Bosch, Rafael; Dorador, Cristina; Gibson, Matthew I.; Christie‐Oleza, Joseph A.
Summary: Pristine marine environments are highly oligotrophic ecosystems populated by well‐established specialized microbial communities. Nevertheless, during oil spills, low‐abundant hydrocarbonoclastic bacteria bloom and rapidly prevail over the marine microbiota. The genus Alcanivorax is one of the most abundant and well‐studied organisms for oil degradation. While highly successful under polluted conditions due to its specialized oil‐degrading metabolism, it is unknown how they persist in these environments during pristine conditions. Here, we show that part of the Alcanivorax genus, as well as oils, has an enormous potential for biodegrading aliphatic polyesters thanks to a unique and abundantly secreted alpha/beta hydrolase. The heterologous overexpression of this esterase proved a remarkable ability to hydrolyse both natural and synthetic polyesters. Our findings contribute to (i) better understand the ecology of Alcanivorax in its natural environment, where natural polyesters such as polyhydroxyalkanoates (PHA) are produced by a large fraction of the community and, hence, an accessible source of carbon and energy used by the organism in order to persist, (ii) highlight the potential of Alcanivorax to clear marine environments from polyester materials of anthropogenic origin as well as oils, and (iii) the discovery of a new versatile esterase with a high biotechnological potential.